KONTRIBUSI PENDAPATAN BUNGA PACAR AIR (PACAH) TERHADAP TOTAL PENDAPATAN RUMAH TANGGA DI BANJAR TEMESI KABUPATEN GIANYAR - Lembayung, I Gede Arga; Vipriyanti, Nyoman Utari; Yudiarini, Nyoman (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
Temesi Village is a part of the population that is farmers. In rural villages some farmers have planted or farmed girlfriend water flowers (Impatiens balsamina). This study aims to find out (1) Analyzing the income of girlfriend water flower farmers (Impatiens balsamina) in Temesi Village, Gianyar District. (2) Analyzing the contribution of income from girlfriend water flower farmers (Impatiens balsamina) to the total income of household income. This research was carried out on girlfriend water flower farmers (Impatiens balsamina) in Temesi Village. This study uses descriptive analysis analysis. Descriptions cover the facts of the farmer's respondents' characteristics such as age, education, and farmer's motivation. Determination of respondents using a census method that records the total number of farmers of girlfriend water flowers (Impatiens balsamina), amounting to 55 people. The results showed that: (1) Motivation of farmers in Temesi Village was high, because farmers were more likely to see favorable results, so they could get favorable results and be able to meet family needs. Revenues to girlfriend water flower farmers (Impatiens balsamina) in Temesi Village are more profitable than other farms, namely by earning an income of Rp 7,781,363 one harvest season. Keywords: Contribution of Pacar Air Flowers (Pacah), Total Household Income.